Evaluating changes in GABAergic and glutamatergic pathways in early life following prenatal stress and postnatal neurosteroid supplementation. (May 2022) - Crombie, Gabrielle K.; Palliser, Hannah K.; Shaw, Julia C.; Hodgson, Deborah M.; Walker, David W.; Hirst, Jonathan J.
Abstract: Background: A correct balance of activity of the GABA and glutamate systems is vital for optimal neurodevelopment and general CNS function, and the dysregulation of this balance has been implicated in a number of neurological conditions. Maternal exposure to stressors is known to have long lasting, deleterious impacts on neurobehaviour, and similarly, results in dysregulation of inhibitory and excitatory pathways in the offspring. The current study aimed to examine effects on these pathways in a guinea pig model of prenatal stress and to elucidate whether increased neuroprotective support by postnatal neurosteroid supplementation would ameliorate adverse outcomes. Methods: Prenatal stress was achieved by exposing pregnant guinea pigs dams to a strobe light for 2hrs/day on gestational age (GA) 50, 55, 60 and 65. Dams were allowed to spontaneously deliver ( GA70) and pups were orally administered either allopregnanolone analogue, ganaxolone (5 mg/kg/day in 45% cyclodextrin), the translocator protein (TSPO) agonist, emapunil (XBD173; 0.3 mg/kg/day in 1% tragacanth gum) or vehicle on postnatal days (PND) 1–7. Hippocampal samples were collected at PND30 to measure relative mRNA expression of components involved in the inhibitory GABAergic pathway and exctitatory glutamatergic pathway by real-time PCR. GABAergic interneurons were quantified by assessing immunohistochemical protein expression of markers parvalbumin, calbindin and calretinin. Results: mRNA expression of GABAergic pathway components at one week of age indicated immature expression profiles of the GABAA receptors as well as decreased GABA synthesis and transport suggesting reduced extrasynaptically-mediated tonic inhibition. Expression profiles of the pathways examined evolved between one week and one month of age but an imbalance in inhibitory/excitatory components persisted. The allopregnanolone analogue ganaxolone offered some protection against excitotoxicity in female hippocampus, however neurosteroid supplementation with ganaxolone or emapunil were unable to fully correct the GABAergic/glutamatergic imbalance observed following prenatal stress. Conclusion: Prenatal stress leads to programmed lasting effects on the major inhibitory and excitatory pathways in the guinea pig brain that continue evolving between the equivalent of early and late childhood. Neurosteroid therapies particularly improved outcomes in females. Further studies are required to identify additional therapeutic targets that are able to fully restore imbalances in the excitatory and inhibitory systems, which may act to prevent development of childhood behavioural disorders. Highlights: Prenatal stress imbalances inhibitory and excitatory systems in the hippocampus. Stress-induced changes persist up until late-childhood equivalence in the guinea pig. Postnatal ganaxolone and emapunil sex-dependently influence long-term outcomes.